Fatores associados à disfunção precoce do enxerto e a sua influência na evolução do transplante de rim - Meira, Fernanda Salazar (2015)
INTRODUCTION: One of the main postoperative complications of kidney transplant is delayed graft function (DGF), which means absence of graft function after transplant or the need for dialysis during the first week post procedure. The occurrence of DGF currently in our hospital is high and has been attributed to a combination of many factors. OBJECTIVE: to evaluate the factors associated to DGF and their influence in the outcome of kidney transplants. METHODS: historical cohort of 150 patients transplanted with live or deceased donor kidneys from 2011 to 2013. RESULTS: DGF was associated to time in dialysis and the number of recipient pre-transplant transfusions, donors age, serum creatinine level, use of vasoactive drugs in the donor, distance from place of organ retrieval and transplant center, and duration of cold ischemia time. DGF influenced post-transplantation outcome in regard to length of stay in intensive care, length of hospital stay, acute rejection episodes, and higher creatinine levels at discharge. Patients and graft survival were shorter in the DGF group. CONCLUSION: There are multiple factors related to DGF, the most important being those related to donors, and organ storage. The most important factor related to the recipient was the dialysis vintage. We did not find a correlation between DGF and HLA-compatibility. DGF consequences are important, including worse graft function and survival, as well as impact in recipient morbidity and mortality.